ZW and XY Sex Chromosomes Drive Rapid and Distinctive Evolution of Sex‐Biased Gene Expression - Kevin Hsiung; Sophie Helen Smith; Astrid Böhne (Molecular Ecology, 2025)
Cichlids are a textbook model system of adaptive radiation and a fascinating example of rapid sex chromosome evolution. Yet in these fish, as in most other taxa, the mechanisms causing sex chromosome turnover and the subsequent impact thereof are unknown. Sexual antagonism was long thought to be a driver of sex chromosome emergence, but experimental support remains scarce. Here, we show that sex‐biased genes, often used as indicators of sexual antagonism, are enriched in three different sex chromosome systems of Lake Tanganyika cichlid species that diverged less than 4 million years ago. Moreover, gene expression is feminised in species that transitioned from an XY to a ZW system on the same chromosome. This is achieved by gain of female‐biased genes, increase of female sex‐bias as well as decrease of male‐bias depending on the tissue investigated. We further show that XY sex chromosomes have more male‐biased genes but without higher intensity of sex‐biased expression. A large fraction of sex‐bias in gene expression evolved adaptively, with a stronger signature in females than males. While we find that sex‐bias in gene expression clearly depends on the heterogametic system, we find only weak support for sex‐biased expression priming chromosomes to become sex chromosomes. Overall, we conclude that there is little evidence that sexual antagonism drives sex chromosome emergence but that it likely plays a role during sex chromosome differentiation. We see rapid emergence of antagonistic expression in sex‐linked genes.